Designing User Experience for a Mobile Application for Agricultural Product Marketing Using the Human-Centered Design Method - Yunianto, Irdha; Wahyudi, Wiwid (International Journal of Graphic Design, 2024)
This research explores the application of Human-Centered Design (HCD) in developing a mobile application for agricultural product marketing, aiming to address critical challenges faced by farmers, such as limited market access and inconsistent internet connectivity. By involving farmers and consumers in each stage of the design process, the application was iteratively improved based on user feedback. The study implemented low-fidelity and high-fidelity prototyping, with five iterations of user testing to enhance usability, navigation, and accessibility. Results show a significant increase in task success rates, user satisfaction, and application efficiency, mainly by including offline features for users in areas with poor internet infrastructure. The study also highlights the effectiveness of HCD in adapting technology to local conditions, offering a practical solution that supports the digital transformation of the agricultural sector, particularly in rural areas. This research contributes to the literature by demonstrating that HCD can be effectively used to develop user-friendly applications that meet the specific needs of the agricultural community